2006
DOI: 10.1007/s10562-005-9187-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sn–Ce/Al2O3 Catalyst for the Selective Catalytic Reduction of NOx Under Lean Conditions

Abstract: Effect of additives, Ce and Mn, on the catalytic performance of Sn/Al 2 O 3 catalyst prepared by sol-gel method for the selective reduction of NO x with propene under lean conditions was studied. Sn-Ce/Al 2 O 3 catalysts exhibited higher activity than Sn/Al 2 O 3 catalyst and the optimum Ce loading is 0.5-1%. The promoting effect of Ce is to enhance the oxidation of NO to NO 2 and facilitate the activation of propene, both of which are important steps for the NO x reduction. The presence of oxygen contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This suggests that the -NCO species is formed by the reaction of NO 3 -and hydrocarbon-derived species. It is evident that the peak area is larger and the rate of formation higher for CeO 2 -SnO 2 /Al 2 O 3 than for SnO 2 / Al 2 O 3 , corresponding to their NO x reduction activities [15].…”
Section: Influence Of Ceo 2 On the Consumption Of Adsorbed Speciesmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that the -NCO species is formed by the reaction of NO 3 -and hydrocarbon-derived species. It is evident that the peak area is larger and the rate of formation higher for CeO 2 -SnO 2 /Al 2 O 3 than for SnO 2 / Al 2 O 3 , corresponding to their NO x reduction activities [15].…”
Section: Influence Of Ceo 2 On the Consumption Of Adsorbed Speciesmentioning
confidence: 98%
“…Our recent research has shown that the addition of 0.5% CeO 2 to a 5% SnO 2 /Al 2 O 3 catalyst significantly improved its NO x reduction activity, especially at low temperatures [15]. However, the mechanistic cause of the promoting effect of CeO 2 is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,4,5] are known to catalyse NO x SCR by hydrocarbons under the conditions of lean-burn engine exhaust. The major drawback of these catalytic systems is their very poor activity at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Selective catalytic reduction of NO x by hydrocarbons (HC-SCR) in the presence of oxygen, a potential method to remove NO x from lean-burn and diesel exhausts, , commonly employs Al 2 O 3 because of the high catalytic activities of its supported metal (Ag, Sn, Ga, In, etc.) oxides for the SCR reaction. Al 2 O 3 also serves as a typical NO x storage and reduction (NSR) catalyst support. According to Westerberg et al, Al 2 O 3 plays an important role as a storage site.…”
Section: Introductionmentioning
confidence: 99%